Deleterious effects of free fatty acids and hydrogen peroxide towards the dinoflagellate Gymnodinium catenatum - Encinas-Yánez, Martín Fernando; Band-Schmidt, Christine Johanna; Zenteno-Savín, Tania; Leyva-Valencia, Ignacio; Fernández Herrera, Leyberth José; Palacios-Mechetnov, Elena (Frontiers in Protistology, 2024)
Allelopathy refers to a biochemical interaction among competing microalgae, it involves a donor species that produces metabolites which can cause inhibitory effects on susceptible species. This phenomenon can participate in the regulation of harmful algal blooms. The dinoflagellate Gymnodinium catenatum is negatively affected by allelopathic interactions with co-occurring microalgae species, like Chattonella marina var. marina, which has been suggested to produce reactive oxygen species (ROS) and free fatty acids (FFA) as toxic and allelopathic agents. This study explored the effect of hydrogen peroxide (H2O2) and the main fatty acids produced by C. marina. An analysis of fatty acids content of C. marina in exponential phase detected 16:0 (12.5 ± 0.01%), 18:4ω-3 (15.4 ± 0.36%) and 20:5ω-3 (35.4 ± 0.71%) as the most abundant. These fatty acids along with H2O2 were used in dose-response bioassays with cultures of G. catenatum in exponential phase. Results suggest that these substances affect cell morphology, including the loss of motility and signs of chlorosis, as well as the chain forming qualities of G. catenatum. Toxicity among these substances varied, suggesting that the polyunsaturated fatty acid 18:4ω-3 can potentially act as a more effective allelochemical (LD50 = 1.7 ± 0.19 mg L -1 at 24 h), followed by 20:5ω-3 (LD50 = 3.6 ± 0.17 mg L -1 at 24 h) and the saturated fatty acid 16:0 (LD50 = 6.2 ± 1.05 at 48 h). Our results suggest these substances can act, at least partially, as allelochemicals, with PUFA being the most effective metabolites. These results contribute in elucidating the potential role of ROS and FFA in allelopathy in marine phytoplankton communities.